The Relationship between Body Mass Index and Left Ventricular Structure and Function in Healthy Adults - Fawzi, Amjad; Aziz, Enaas S. (Journal of the Faculty of Medicine Baghdad, 2011)
Background: There is considerable evidence which associate cardiovascular morbidity and mortality with obesity, however, a direct effect of uncomplicated obesity on cardiac function is not well established. Objective: To evaluate the relationship between body mass index (BMI) and left ventricular structure and function. Methods: This cross-sectional study was carried out on (146) apparently healthy adults from both sexes (85 male and 61 female) aged 20-59 years(36.49±9.92 ). Subjects were grouped according to BMI into1.normal weight group included 47 subjects (BMI=18.5-24.9Kg/m2);2. Overweight group included 43 subjects (BMI=25-29.5 Kg/m2) and 3. obese group included (56) subjects(BMI≥30). Echocardiographic indices of left ventricular structure and function were obtained. This study was performed between October 2009 till April 2010 at the Echocardiography Unit in Ibn Sina Teaching Hospital in Mosul. Results: There was a significant increase in LVM(left ventricular mass), LVMI(left ventricular mass index), LVIDD(left ventricular internal dimension in diastole) and PWT(posterior wall thickness) among over weight and obese subjects (P< 0.001),however, both contractility indices [LVEF%(left ventricular ejection fraction percent) and LVFS %(left ventricular fractional shortening percent)] seemed unchanged significantly. The left ventricular diastolic function [E/A ratio(ratio of passive to active velocity inflow)] has significantly decreased among the obese group (P< 0.001). This observed decrease in E/A ratio with increasing BMI coincided with a statistically significant increase (P< 0.001) in LAD (left atrial dimensions). Conclusions: Increased body weight is positively correlated with LVM but not with systolic dysfunction. All subjects with isolated obesity have subclinical left ventricular diastolic dysfunction; this correlates with BMI.